2017
DOI: 10.1186/s41016-017-0090-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HLA-DR genes in gliomas: correlation with clinicopathological features and prognosis

Abstract: Background: Human leukocyte antigen (HLA)-DR is a classical major histocompatibility complex (MHC) class II molecule encoded by five genes: HLA-DRA, HLA-DRB1, HLA-DRB3, HLA-DRB4 and HLA-DRB5. The current study aimed to investigate the role of these genes in gliomas by analyzing microarray data. Methods: We enrolled 305 patients with histologically confirmed gliomas, and performed microarray data analysis along with studying their clinical characteristics. A new variable, termed HLA-DR score, was defined to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
(42 reference statements)
0
12
0
Order By: Relevance
“…Ninety-one differentially expressed immune genes (DEIGs) were then selected using the ImmPort database [ 18 ] ( Figure 3A , 3B ). The DEIGs were uploaded to the Metascape website to identify Gene Ontology (GO) Terms and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ninety-one differentially expressed immune genes (DEIGs) were then selected using the ImmPort database [ 18 ] ( Figure 3A , 3B ). The DEIGs were uploaded to the Metascape website to identify Gene Ontology (GO) Terms and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Genes with log2 |fold change| ≥1 and False Discovery Rate (FDR) <0.05 were selected as differentially expressed genes (DEGs). DEIGs were identified by the ImmPort database ( https://www.immport.org/ ) [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…We also found that a) PD-1/PD-L1 interaction score may be a predictor of OS in recurrent GBM patients who received anti-PD-1 therapy, b) HLA-DR is associated with worse OS in recurrent GBM patients who received anti-PD-1 therapy, and c) the coexpression of PTEN loss and Ki67+ tumor and non-tumor cells may provide a more speci c marker of immunosuppression in the GBM microenvironment. HLA-DR is a generic, non-speci c biomarker in GBM; however, Fan et al prove that an increased HLA-DR score was correlated with a more aggressive glioma tumor grade [17]. Additionally, they investigated whether HLA-DR scores predicted survival in GBM patients treated with immunotherapy but found no signi cant difference in the prognosis of subgroups with high and low HLA-DR scores.…”
Section: Discussionmentioning
confidence: 99%
“…HLA-DR is a generic, non-speci c biomarker in GBM; however, Fan et al prove that an increased HLA-DR score was correlated with a more aggressive glioma tumor grade [17]. Additionally, they investigated whether HLA-DR scores predicted survival in GBM patients treated with immunotherapy but found no signi cant difference in the prognosis of subgroups with high and low HLA-DR scores.…”
Section: Discussionmentioning
confidence: 99%